Changes in Performance of Apical Suspension at the Time of Surgery for Prolapse: Assessment of the Influence of the American Urogynecologic Society and American College of Obstetricians and Gynecologists Practice Bulletin. Issue 6 (3rd June 2022) - Luchristt, Douglas; Zemtsov, Gregory; Jelovsek, J. Eric
Abstract : Objectives: To assess the association of publication of the American Urogynecologic Society (AUGS)/American College of Obstetricians and Gynecologists (ACOG) Practice Bulletin on pelvic organ prolapse and performance of an apical suspension at the time of surgery for pelvic organ prolapse. Methods: Surgical procedures performed with a primary diagnosis of uterovaginal or female genital prolapse, cystocele, or enterocele were isolated from the 2011 to 2019 American College of Surgeons National Surgical Quality Improvement Program Database. An autoregressive interrupted time series regression estimated the overall temporal trend in performance of an apical suspension and assessed for a change in trend associated with publication of the AUGS/ACOG Practice Bulletin in April 2017. A stratified analysis was also performed depending on performance of a concomitant hysterectomy, and sensitivity analysis was performed using only diagnoses of uterovaginal or vaginal vault prolapse. Results: There were 72, 194 individuals identified; 83.4% had a diagnosis of uterovaginal or female genital prolapse, 15.2% cystocele and 1.4% enterocele. Only 36.6% of cases had an apical suspension. Prior to the practice bulletin publication, performance of an apical suspension grew at 0.19% per quarter (95% confidence interval [CI], 0.07–0.31), with a trend toward increased utilization (+0.12%; 95% CI, −0.06 to 0.30) after publication. The increase was greater among cases with a concomitant hysterectomy (+0.35%; 95% CI, 0.08–0.62). Sensitivity analyses found similar changes in trend. Conclusions: Performance of apical suspensions during surgery for prolapse remains low and is increasing at less than 1% per year. The AUGS/ACOG practice guidelines were associated with minimal changes in this pattern. Incentives or other strategies may be needed to further encourage standard of care management of prolapse.